Female sexual dysfunction in systemic sclerosis: The role of endothelial growth factor and endostatin. Issue 1 (February 2019) - Gigante, Antonietta; Navarini, Luca; Margiotta, Domenico; Barbano, Biagio; Afeltra, Antonella; Rosato, Edoardo
Introduction: Since female sexual dysfunction in systemic sclerosis women is multifactorial, we can assume that vascular damage may play a role in pathogenesis. The aim of the study was to evaluate the clitoral blood flow, by Echo color Doppler, and to correlate it whit serum levels of vascular endothelial growth factor and endostatin. Methods: A total of 15 systemic sclerosis women and 10 healthy controls matched for sex and age were enrolled in this study. Serum VEGF165 and endostatin levels were determined in systemic sclerosis patients by commercial enzyme-linked immunosorbent assay kit. Clitoral blood flow was measured by Doppler indices of clitoral artery: pulsatile index, resistive index, and systolic/diastolic ratio were measured. Sexual dysfunction was assessed by Female Sexual Function Index. Results: Vascular endothelial growth factor (pg/mL) and endostatin (ng/mL) median values were significantly higher in systemic sclerosis women than healthy controls. Resistive index and systolic/diastolic ratio median values were significantly higher in systemic sclerosis women than healthy controls. Negative correlation exists between serum levels of vascular endothelial growth factor and resistive index (r = −0.55, p < 0.05). Positive correlation was observed between serum levels of endostatin and resistive index (r = 0.70, p < 0.01) and systolic/diastolic ratio (r = 0.77, p < 0.01). Discussion: We can suppose that clitoral blood flow in systemic sclerosis women is reduced not only for macro- and microvascular damage but also for impaired angiogenesis.